Extending the Theory of Planned Behavior: Predicting Young Consumer Purchase Behavior of Energy-Efficient Appliances (Evidence From Developing Economy). (February 2022) - Bhutto, Muhammad Yaseen; Soomro, Yasir Ali; Yang, Hailan
Global electricity consumption has increased dramatically in the past few decades, resulting in many countries considering energy efficiency as the only solution to tackle issues related to energy and pursue sustainable development goals. However, there is a shortage of studies at the household level on the propensity to use energy-efficient appliances (EEA), especially for developing countries, which have great potential for EEA adoption and usage. Besides, young consumers form an important part of developing countries' population as well as the next generation of consumers. Yet studies examining their inclination toward more sustainable products such as EEA remain scarce. This study employs data gathered from a survey questionnaire among 240 young Pakistani consumers to explain EEA adoption by focusing on extended version of the theory of planned behavior (TPB), incorporating additional variables such as self-expressive benefits, utilitarian environmental benefits and moral obligations. The results show that utilitarian environmental benefits significantly influence attitudes, whereas self-expressive has an insignificant influence on attitude. Along with this study found moral obligation also has an insignificant impact on subjective norms. Finally, the study revealed the impact of purchase intention of EEAs on the purchase behavior of EEAs. Therefore, the results of this study present a novel understanding for Pakistani policymakers should pay more attention on shaping consumer attitudes, social values and perceived behavioral control, which will eventually drive energy-efficient appliance purchasing behavior.